Perching aircraft dynamics and control optimization - Mau, Zao Min. (2009)
This final year project covers the optimization of aircraft perching maneuver through geometric reconfiguration or morphing. A novel Unmanned Aerial Vehicle (UAV) model which adopts canard configuration and variable-incidence outer wings is specially designed for the analysis of perching maneuver. As opposed to thrust vectoring technique, perching involves high angle of attack maneuver and control to bring down the speed of low thrust-to-weight ratio UAV by utilizing high aerodynamic drag. In order to achieve short landing distance effectively and efficiently, with low touchdown velocity, the main goal of this study is to determine the optimal perching control scheme which results in the smallest possible spatial bounds. For better insights of perching maneuver, nonlinear aerodynamic model with the incorporation of dynamic stall effects is used to predict the behavior of the UAV in post-stall regime. In this project, empirical methods are primarily used to model the aerodynamics of attached and separated flow regimes. By means of direct collocation method and sequential quadratic programming, the optimal trajectories for fixed and morphed configurations are determined and compared. Besides, to obtain useful trends, the optimal solutions of varying control capability, thrust-to-weight ratio and normal load factor are also compared, discussed and generalized. Additionally, the effects of constraints relaxation such as the degree of flow separation on flight performance is presented. Based on the results, improved UAV designs which better suit the purpose of perching maneuver are suggested for future analysis. Generally, it is demonstrated that the dynamic effects of flow separation and the capability to morph have significantly reduced the spatial bounds and enhanced the success of perching maneuver. Furthermore, it is shown that in the absence of high thrust, the UAV can still achieve the effects of VSTOL by harnessing the advantages of aerodynamic braking in the post-stall regime through vehicle morphing.